Volar Lunate Dislocation Causing Secondary Carpal Tunnel Syndrome: A Case Report - Gabig, Andrew M.; Cooke, Hayden L.; Roundy, Robert; Gottschalk, Michael B. (Journal of Wrist Surgery, 2023)
Background Failure of carpal tunnel release is an uncommon occurrence with unique pathologies that may impede proper diagnosis and treatment. Symptoms are most often attributed to an inadequate release of the transverse carpal ligament or pathologic scar tissue resultant of the primary decompression.Case Description In this report, we describe the case of a 79-year-old male with a history of scaphoid lunate advanced collapse and a prior carpal tunnel decompression presenting with worsening right wrist function and new right palmar mass. The patient had no significant antecedent trauma, and clinical workup revealed volar dislocation of the lunate. After failed conservative treatment and multiple ultrasound-guided corticosteroid injections, the patient was successfully treated surgically with carpal tunnel release, tenosynovectomy, and lunate excision.Literature Review Volar lunate dislocation without a traumatic mechanism is rare. Progressive carpal destabilization and volar subluxation is not a commonly reported cause of secondary carpal tunnel symptoms. Isolated reports in the literature have been published with nearly identical presentations. Kamihata et al reported a patient, with a history of carpal tunnel decompression, presenting with numbness and tingling in her right hand without traumatic injury. A displaced lunate was found to abut the flexor tendons and median nerve. Ott et al further reported an atraumatic lunate dislocation and palmar swelling 4 weeks after a carpal tunnel release.Clinical Relevance In the setting of existing arthritic degeneration, carpal tunnel release may destabilize the carpus and predispose patients to carpal dislocation. Further research is required to understand the risks associated with this instability leading to lunate dislocations secondary to carpal tunnel release.
Keywords: carpal tunnel release; recurrent carpal tunnel syndrome; atraumatic; lunate dislocation; carpal instability